Genre et islamophobie Discriminations, préjugés et représentations en Europe - Lépinard, Éléonore; Sarrasin, Oriane; Gianettoni, Lavinia (Sociétés, Espaces, Temps, 2021)
The first book offering a study of the gendered aspects of Islamophobia in France, Switzerland and Belgium, this book brings together contributions from sociology and social psychology. It analyses the processes by which anti-Muslim discrimination and prejudice are elaborated and relayed, both by institutional players and citizens, and the ways in which those they target resist them. Gender is omnipresent in the debates on Islam and the integration of Muslims in European countries, both regarding the forms of Islamic veils and the legislation to prohibit them. It is thus at the heart of the development of the specific form of racism and racialisation known as Islamophobia. How can Islamophobia be identified in gendered public and media discourse? How is it relayed in ordinary discourse attributing specific sexism and patriarchy to Muslim men? What discriminations are experienced by Muslim women, whether veiled or not, and how do they differ from those experienced by Muslim men?